Preoperative lymphopaenia, mortality, and morbidity after elective surgery: systematic review and meta-analysis. (July 2021) - Schroth, Johannes; Weber, Valentin; Jones, Timothy F.; Del Arroyo, Ana Gutierrez; Henson, Sian M.; Ackland, Gareth L.
Abstract: Background: In the general adult population, lymphopaenia is associated with an increased risk for hospitalisation with infection and infection-related death. The quality of evidence and strength of association between perioperative lymphopaenia across different surgical procedures and mortality/morbidity has not been examined by systematic review or meta-analysis. Methods: We searched MEDLINE, Embase, Web of Science, Google Scholar, and Cochrane databases from their inception to June 29, 2020 for observational studies reporting lymphocyte count and in-hospital mortality rate in adults. We defined preoperative lymphopaenia as a lymphocyte count 1.0–1.5×10 9 L −1 . Meta-analysis was performed using either fixed or random effects models. Quality was assessed using the Newcastle–Ottawa Scale. The I 2 index was used to quantify heterogeneity. The primary outcome was in-hospital mortality rate and mortality rate at 30 days. Results: Eight studies met the inclusion criteria for meta-analysis, comprising 4811 patients (age range, 46–91 yr; female, 20–79%). These studies examined preoperative lymphocyte count exclusively. Studies were of moderate to high quality overall, ranking >7 using the Newcastle–Ottawa Scale. Preoperative lymphopaenia was associated with a threefold increase in mortality rate (risk ratio [RR]=3.22; 95% confidence interval [CI], 2.19–4.72; P <0.01, I 2 =0%) and more frequent major postoperative complications (RR=1.33; 95% CI, 1.21–1.45; P <0.01, I 2 =6%), including cardiovascular morbidity (RR=1.77; 95% CI, 1.45–2.15; P <0.01, I 2 =0%), infections (RR=1.45; 95% CI, 1.19–1.76; P <0.01, I 2 =0%), and acute renal dysfunction (RR=2.66; 95% CI, 1.49–4.77; P <0.01, I 2 =1%). Conclusion: Preoperative lymphopaenia is associated with death and complications more frequently, independent of the type of surgery. Prospero registry number: CRD42020190702.